Penerapan Reflexive Law Dalam Upaya Menjamin Keterbukaan Informasi Di Lingkungan Pengadilan - Ashfa Azkia (Lex Renaissance, 2021)
Judicial transparency for the Supreme Court is not only a public need but also the needs of all members of the judiciary. With judicial transparency, there will be a gradual strengthening of accountability and professionalism as well as the integrity of the judiciary. The problems studied is how does reflexive law answer the problem of public information disclosure in the judiciary? From the results of the analysis of the study, it is concluded that the effort to realize public information disclosure before the court was applied by using a reflexive law approach. This theoretical approach is manifested in self-regulation in the form of the Decree of the Chief Justice of the Supreme Court of the Republic of Indonesia Number 1-144/KMA/SK/I/2011 on Guidelines for Information Services in Courts. Law Number 14 of 2008 on Public Information Disclosure does not regulate in detail and technically the provisions of public information disclosure services in each public agency, public bodies are required reflexively to make rules on standard operating procedures that regulate information service systems to the public through Information Commission Regulation Number 1 of 2010 on Public Information Service Standards.Key Words: Ccourt; information disclosure; reflexive lawAbstrakTransparansi peradilan bagi Mahkamah Agung bukan saja menjadi kebutuhan publik tetapi juga kebutuhan seluruh warga badan peradilan. Dengan adanya transparansi peradilan, secara perlahan akan terjadi penguatan akuntabilitas dan profesionalisme serta integritas warga peradilan. Permasalahan yang diteliti, bagaimana reflexive law menjawab permasalan keterbukaan informasi publik di lingkungan peradilan? Dari hasil analisis kajian, disimpulkan bahwa upaya perwujudan keterbukaan informasi publik di lingkungan pengadilan, diterapkan menggunakan pendekatan reflexive law. Pendekatan teori ini termanifestasikan dalam self regulation yang berupa Surat Keputusan Ketua Mahkamah Agung Republik Indonesia Nomor 1-144/KMA/SK/I/2011 Tentang Pedoman Pelayanan Informasi Di Pengadilan. Undang-Undang Nomor 14 tahun 2008 tentang Keterbukaan Informasi Publik tidak mengatur secara rinci dan teknis tentang ketentuan pelayanan keterbukaan informasi publik di masing-masing badan publik, badan publik diwajibkan secara refleksif untuk membuat aturan tentang prosedur standar operasional yang mengatur sistem pelayanan informasi kepada publik melalui Peraturan Komisi Informasi Nomor 1 Tahun 2010 Tentang Standar Layanan Informasi Publik.Kata Kunci: Reflexive law; keterbukaan informasi; pengadilan